Low cost 'green' dye sensitized solar cells based on New Fuchsin dye with aqueous electrolyte and platinum-free counter electrodes. (August 2019) - Kokal, Ramesh K.; Bhattacharya, Somdatta; Cardoso, Lilian S.; Miranda, Paulo B.; Soma, Venugopal Rao; Chetti, Prabhakar; Melepurath, Deepa; Raavi, Sai Santosh Kumar
Highlights: New Fuchsin dye is used as a photosensitizer in aqueous DSSC for the first time. Photophysics of NF were studied using DFT and various spectroscopy techniques. DSSC were fabricated using Fe 3+ /Fe 2+ in water based electrolyte and CoS/C-fabric as CE η  = 2.9% was achieved. The various components used are cheap and eco-friendly and hence the title low cost "green" DSSC . Abstract: In this work, we present the application of a inexpensive water-soluble New Fuchsin (NF) dye as a photosensitizer for dye sensitized solar cells (DSSC). A comprehensive study including computational, spectroscopy and cyclic voltammetry measurements established the efficacy of NF as a photosensitizer. Density functional theory (DFT) modelling of NF is performed to estimate the energy levels and experimentally verified using the cyclic voltammetry measurements. For the spectroscopy characterization time-resolved absorption and fluorescence studies are employed on NF in ethanol solution and as thin film deposited on glass and mesoporous TiO2 . Femtosecond transient absorption measurements revealed ultrafast electron injection within <1 ps at the interface of NF and TiO2 . NF sensitized solar cells were fabricated and optimised using various liquid electrolytes and carbon-based counter electrodes. The fabricated devices were further characterized using electro-impedance spectroscopy and Mott-Schottky measurements. The best-performing device with photo-conversion efficiency of 2.9% was obtained using aqueous Fe 3+ /Fe 2+ electrolyte and CoS treated carbon fabric. These components are non-toxic and economical resulting in the fabrication of low cost and eco-friendly "green"solar cells.